Ancient Giant Sequoias Are Dying: Scientists Refuse to Acknowledge the Cause - Herndon, J. Marvin; Williams, Dale D.; Whiteside, Mark (Advances in Social Sciences Research Journal, 2021)
California’s Giant Sequoias and Coast Redwoods, long symbols of strength, longevity, and resilience, have survived natural climate change for as long as 3,000 years, but are now succumbing to human manipulation of the natural environment. Scientists concerned with the wellbeing of these magnificent trees blame their recent die-offs on climate change, drought, and insects while turning a blind eye to the primary underlying cause: environmental modification by jet-emplacement in the troposphere of toxic particles evidenced as coal combustion fly ash. Said aerosolized particulates cause droughts and deluges, heat the troposphere, contaminate rain, snow, and fog with plant-killing toxins including chemically-mobile aluminum, coat foliage, and exacerbate forest fires. The aerial spraying depletes stratospheric ozone, allowing damaging ultraviolet radiation B and C to reach Earth’s surface. These environmental stressors weaken the trees to the point they are attacked by insects and pathogenic fungi. Here we disclose the unspoken, underlying cause of the die-offs of Giant Sequoias and Coast Redwoods. Through a diabolically-deceptive, Trojan horse, United Nations’ International Treaty the governments of sovereign nations were coerced to wage environmental warfare against their own citizens and the natural environment under the guise of peaceful environmental modification. Remaining trees, and indeed much of the life on Earth, can only be saved if this environmental modification is halted.